Design Meets Neuroscience: An Electroencephalogram Study of Design Thinking in Concept Generation Phase - Hu, Ying; Ouyang, Jieqian; Wang, Huazhen; Zhang, Juan; Liu, An; Min, Xiaolei; Du, Xing (Frontiers in Psychology, 2022)
Extant research on design thinking is subjective and limited. This manuscript combines protocol analysis and electroencephalogram (EEG) to read design thoughts in the core design activities of concept generation phase. The results suggest that alpha band power had event related synchronization (ERS) in the scenario task and divergent thinking occupies a dominant position. However, it had event related desynchronization (ERD) in analogy and inference activities, etc., and it is stronger for mental pressure and exercised cognitive processing. In addition, the parietooccipital area differs significantly from other brain areas in most design activities. This study explores the relationship of different design thinking and EEG data, which is innovative and professional in the field of design, providing a more objective data basis and evaluation method for future applied research and diverse educational practices.